Cetyltrimethylammonium chloride influence on silica optical fiber strength - El Abdi, R.; Rujinski, A.D.; Boumbimba, R.M.; Poulain, M. (Фізико-хімічна механіка матеріалів, 2013)
The evolution of silica optical fibers strength aged in cetyltrimethylammonium chloride solution (CTAC) are investigated. The mechanical behaviour of silica coated and naked fibers in contact with CTAC solution at different concentrations is studied. Result analysis proves that the immersion in CTAC drastically decreases the fiber strength and specially near the critical micelle concentration point (CMC). Beyond CMC point, a small increase of fiber strength is analyzed and commented. Based on analysis of aged fiber surface morphology obtained from Scanning Electron Microscopy, the damage extent on fiber core and polymer coatings is observed.